2005
DOI: 10.1074/jbc.m508816200
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Sulfation Pattern of Chondroitin Sulfate by Uronosyl 2-O-Sulfotransferase

Abstract: We have shown previously that a highly sulfated sequence, GalNAc(4,6-SO 4 )-GlcA(2SO 4 )-GalNAc(6SO 4 ), is present at the nonreducing terminal of chondroitin sulfate (CS), and this structure was synthesized from a unique sequence, GalNAc(4SO 4 )-GlcA(2SO 4 )-GalNAc(6SO 4 ), by sulfation with N-acetylgalactosamine 4-sulfate 6-O-sulfotransferase. Uronosyl 2-O-sulfotrasferase (2OST), which transfers sulfate from 3-phosphoadenosine 5-phosphosulfate (PAPS) to position 2 of the GlcA residue of CS, is expected to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 45 publications
(54 reference statements)
3
16
1
Order By: Relevance
“…This result correlates well with the mRNA data, since this enzyme has only one isoform in most of the genome-sequenced organisms, in contrast to multiple isoforms for almost all other HS and CS sulfotransferases [39]. CS-2OST transfers the sulfo group to the 2-OH position of the hexuronic acid that is adjacent to an Nacetylated galactosamine residue (GalNAc) carrying either a 6-O or 4-O sulfo group [41,42] and CS chains with 2-O-sulfo group exhibits a variety of biological functions [43,44,45]. In pre-eclampsia, the absence of 2-O-sulfo groups may reflect the fine tuning of CS chain that normally occurs in gravid placenta.…”
Section: Discussionsupporting
confidence: 73%
“…This result correlates well with the mRNA data, since this enzyme has only one isoform in most of the genome-sequenced organisms, in contrast to multiple isoforms for almost all other HS and CS sulfotransferases [39]. CS-2OST transfers the sulfo group to the 2-OH position of the hexuronic acid that is adjacent to an Nacetylated galactosamine residue (GalNAc) carrying either a 6-O or 4-O sulfo group [41,42] and CS chains with 2-O-sulfo group exhibits a variety of biological functions [43,44,45]. In pre-eclampsia, the absence of 2-O-sulfo groups may reflect the fine tuning of CS chain that normally occurs in gravid placenta.…”
Section: Discussionsupporting
confidence: 73%
“…Unlabeled PAPS was a gift from YAMASA Corp. (Choshi, Japan). N-Acetylgalactosamine 4,6-bissulfate was prepared from ⌬Di-diS E , as described previously (37).…”
Section: Methodsmentioning
confidence: 99%
“…Sulfation of position 6 of the nonreducing terminal GalNAc(4SO 4 ) in the unique sequence found in the nonreducing terminal of CS, GalNAc(4SO 4 )-GlcA(2SO 4 )-GalNAc(6SO 4 )-, by GalNAc(4SO 4 ) 6-O-sulfotransferase was markedly stimulated by the penultimate GlcA(2SO 4 ) residue (17). Uronosyl 2-O-sulfotransferase selectively transferred sulfate to GlcA located in a unique sequence in CS, GalNAc(4SO 4 )-GlcA-GalNAc(6SO 4 ) (12). These observations strongly suggest that the order of participation of each sulfotransferase into the biosynthetic steps should be important to elaborate the functional fine structures in CS.…”
Section: Chondroitin Sulfate (Cs)mentioning
confidence: 99%
“…Subcellular localization of these sulfotransferases is probably relevant to determining the order. The purified C6ST-1, C4ST-1, and GalNAc(4SO 4 ) 6-O-sulfotransferase (18 -20) as well as the recombinant C6ST-1, C4ST-1, GalNAc(4SO 4 ) 6-O-sulfotransferase, and uronosyl 2-O-sulfotransferase (12,16,17) have been found to be glycoproteins containing relatively abundant N-linked oligosaccharides. It has been reported that N-glycans contained in various glycoproteins are involved in protein folding, ER-associated protein degradation, intracellular trafficking, and production of functional proteins (21)(22)(23)(24)(25).…”
Section: Chondroitin Sulfate (Cs)mentioning
confidence: 99%
See 1 more Smart Citation